Pengembangan Teknologi Pembelajaran PAI pada Generasi Alpha Berbasis 3N (Niteni, Nirokke, Nambahi) dalam Perspektif Ki Hajar Dewantara - Muhammad Faiz Nurfalahi; Linda Puspitasari; Agus Nuril Anwar; Uchik Rini Qomaria; Sita Acetylena (Jurnal Wahana Literasi Pendidikan, 2026)
This study is motivated by the challenges of Islamic Religious Education (PAI) learning in addressing the characteristics of Generation Alpha, who are considered digital natives a term referring to a generation born and raised in the digital era. On the one hand, technology offers learning effectiveness; on the other hand, it poses risks to the erosion of character and moral values. This study aims to analyze the challenges of PAI learning for Generation Alpha and to formulate a development model through the perspective of Ki Hajar Dewantara’s educational philosophy. The method used is qualitative with a library research approach, in which the primary data source refers to the book Karya Ki Hadjar Dewantara, Bagian Pertama: Pendidikan. The findings reveal that Dewantara’s concept of “Kodrat Zaman” legitimizes the use of technology, while “Kodrat Alam” and the “Among System” function as moral filters and character-guidance frameworks. The 3N strategy (Niteni, Nirokke, Nambahi) is proposed as an operational model in PAI technology, enabling students to shift from passive digital consumers to creative producers of da’wah content. The study concludes that the integration of PAI technology from Dewantara’s perspective is capable of creating adaptive learning while remaining rooted in the cultivation of noble character.